2015
DOI: 10.1016/j.jaap.2014.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and identification of urushi using in situ pyrolysis/silylation–gas chromatography–mass spectrometry

Abstract: a b s t r a c tAnalytical pyrolysis coupled with gas chromatography and mass spectrometry is a very powerful tool to analyze polymers and macromolecules. In this paper this technique was applied to the characterization of the urushi oriental lacquer (qi-lacquer in Chinese) with the aim to set up an alternative analytical method to identify the lacquer.Urushi is mostly rich in alcoholic polar moieties, thus, a derivatization step is required, which is crucial for the detection and MS identification of all the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…The formation of mono-TMS catechols can be attributed to steric hindrance effects and was also revealed in the analysis of urushi from Rhus Vernicifera [23]. Of the mono-TMS alkylcatechols (Figure 2), several saturated and unsaturated compounds, mostly appearing as pair peaks, were identified for both the Burmese and the Vietnamese lacquers.…”
Section: Mono-tms Alkylcatecholsmentioning
confidence: 80%
See 4 more Smart Citations
“…The formation of mono-TMS catechols can be attributed to steric hindrance effects and was also revealed in the analysis of urushi from Rhus Vernicifera [23]. Of the mono-TMS alkylcatechols (Figure 2), several saturated and unsaturated compounds, mostly appearing as pair peaks, were identified for both the Burmese and the Vietnamese lacquers.…”
Section: Mono-tms Alkylcatecholsmentioning
confidence: 80%
“…Both pyrograms showed different classes of pyrolysis products, mainly mono-TMS alkylcatechols, bis-TMS alkylcatechols, TMS alkylphenols, alkylbenzenes and aliphatic hydrocarbons, arising from the pyrolytic cleavages of C-C and C-O bonds present in the polymeric network of the oriental lacquers. In a previous work [23] we showed that the extraction of specific m/z values enabled pyrolytic profiles of these characteristic pyrolysis products to be highlighted in urushi samples, which could be used for diagnostic purposes. In particular, m/z 179, 253, 180, 91 and 57 were used to extract the pyrolytic profiles of mono-TMS alkylcatechols, bis-TMS alkylcatechols, TMS alkylphenols, alkylbenzenes, and aliphatic hydrocarbons respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations